ISOLATION, IDENTIFICATION AND CONSERVATION OF POTENT HYDROLASE PRODUCER FROM DIFFERENT SOILS OF ODISHA, INDIA - BIJAY KUMAR SETHI,; PRATIVA KUMARI NANDA,; SANTILATA SAHOO, (International Journal of Pharma and Bio Sciences, 2013)
In this investigation, innate fungal species were isolated from soils of Odisha and screened for their hydrolytic potentials. Utmost numbers of fungi were isolated from botanical garden soil (3 × 108 CFU/g), Post Graduate Department of Botany, Utkal University, Odisha, India. Among 35 fungal taxa, Aspergillus niger was most predominant mycoflora followed by Aspergillus terreus. All fungal isolates were accredited to nine genera like Alternaria, Curvularia, Fusarium and Mucor represented two taxa, Penicillium by four taxa, Rhizopus by 3 taxa and Trichoderma represented one species. Aspergillus species were dominant groups that represented about 18 taxa. All isolates were screened for hydrolytic competence and most of the isolates biosynthesized one or more hydrolytic enzymes. Aspergillus terreus exhibited splendid diversity in biosynthesis of all investigated hydrolases. Hence, A. terreus could be a prospective contender in biosynthesizing high valued-low cost industrial enzymes from cheapest substrates addressing the welfare of mankind.